Use of kinesiology taping in different diseases - Piotr Jaworski (Kazimierz Wielki University, 2019)
Kinesiology taping, called in Poland more and more often dynamic plastering is a method with a very wide application. More and more often this method is noticed among patients. Currently, many studies have been conducted, in which the effectiveness of therapy with the use of tapes for kinesiology taping has been proven. What is more, no harmful effects of this form of therapy have been found. In addition, there is more and more research showing the effectiveness of cathodiology taping as a form of supporting the effects of the main therapy. The paper was written on the basis of review articles and research papers presented in reputable Polish magazines dealing with physiotherapy.